La gobernanza regional compleja del comercio electrónico latinoamericano: una perspectiva comparada de la Alianza del Pacífico, la Comunidad Andina y el Mercosur - Julissa Castro-Silva (Colombia Internacional)
Objective/context: The proliferation in the number, depth, and scope of e-commerce agreements has integrated shared agendas and memberships within Latin America’s complex regional governance, making cooperation and fragmentation non-exclusive practices. Therefore, this article asks about the conditions that have facilitated or limited the development of a Latin American digital market. Methodology: A comparative qualitative analysis of the Pacific Alliance, the Andean Community, and Mercosur, together with process tracing, will shed light on their progress in this area, taking into account the degree of linkage they maintain with three mechanisms that foster collaboration and coordination dynamics among various institutions an d actors. Conclusions: The analysis shows that, within systems characterized by growing institutional density and diversity—such as the Latin American e-commerce environment—regional cooperation can be facilitated when regional trade agreements are embedded in a broader trade regime, where there is a clear sequencing among different agreements, and when orchestrators and policy networks are present. In contrast, their absence leads to ineffective agreement implementation and increased regional fragmentation. Originality: This work connects studies on complex regional governance with a relatively underexplored agenda in Latin American academic literature: e-commerce.